Hubungan Komunikasi Guru dan Anak dengan Kedisiplinan pada Kelompok B - Binti Ni’matul Muthoharoh; Siti Fadjryana Fitroh; Dewi Mayangsari (PG-PAUD Trunojoyo, 2019)
: The aim of this research to determine the correlation of communication between teachers and children with discipline of group B in Sejahtera Kamal kindergarten. This type of research is quantitative correlation design. The sampling technique used nonprobability samples with the type of saturated sample of 16 samples. Data collection techniques using observation, questionnaires, and documentation. Observation sheet used to measure variables discipline children at school and questionnaires used to measure the communication variables of teachers and children. Documentation use to photo of activities. Data were analyzed using Pearson Product Moment Correlation to test the hypothesis. The results showed that no significant relationship between teacher and child communication discipline within the group B in Sejahtera Kamal kindergarten. The result of the data analysis Pearson Product Moment Correlation was obtained for